Modernisation or Westernisation of Johor under Abu Bakar: A Historical Analysis - A Rahman Tang Abdullah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences International Islamic University Malaysia, 2008)
The transformation of Johor under Abu Bakar has been variously described as modernisation or westernisation. Westernisation argument is flawed because during the period under consideration, Johor was not yet fully under the control of the West. The archival records show that Johor’s transformation was self-initiated to promote the welfare of the people. The reforms Abu Bakar brought about in Johor affected more the Malay culture than Islamic rules and practices. Even then these reforms not simply modernised but elevated the position of certain aspects of Malay culture. It is, therefore, appropriate to describe Abu Bakar as the father of modern Johor.